Bricolage concept in risk culture assessment - Gorzeń Mitka, Iwona (European Journal of Sustainable Development, 2017)
When faced with challenging conditions in which companies operate today, rapid access to various forms of resource can be a key determinant of organisational resilience on risk. Management of risk is considered to be a powerful instrument for sustainable development in organization. The concept of bricolage offers the potential to better understanding of organisational resourcefulness in a time of disruption. The study includes the research results concerning the identification of correlations between bricolage and the attitude as to risk as a key element of forming the risk management culture in the practice of Polish small and medium sized enterprises from the point of view of a balanced development. An additional goal of this research is to, at least partially, fill the gap in researches in terms of risk management. The research findings indicate that an approach to decision processes in the context of bricolage and an attitude towards risk are indeed dependent of one another. Key words: bricolage, management, environment, decision-making processes, risk culture